ANALISIS KEPUASAN DAN MINAT BELAJAR MAHASISWA PADA PERKULIAHAN KALKULUS MENGGUNAKAN MODEL NUMBER HEAD TOGETHER - Faradiba Jabnabillah; Andini Setyo Anggraeni; Sabarinsyah Sabarinsyah; Alhamidi Alhamidi (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
The aim of this research is to describe the differences in the average scores of student satisfaction and interest in learning in Calculus lectures using the Number Head Together (NHT) type learning model. This research uses an experimental method using One Group Pretest Posttest Design. The data analysis used in this research is the paired t-test (Paired Sample t-Test). The research subjects were 42 people, namely students of the Industrial Engineering study program, semester one of the 2022-2023 Academic Year. The research results showed that the average pretest score from the student satisfaction questionnaire was 18.3810, while the average posttest score from the student satisfaction questionnaire was 35.4524. This shows that the average posttest score for student satisfaction is higher than the average pretest score for student satisfaction using the NHT model in calculus lectures. Furthermore, the average pretest score from the student interest in learning questionnaire was 20.1429. Meanwhile, the average posttest score resulting from the student interest in learning questionnaire was 35.6905, this shows that the average posttest score for student interest in learning was higher than the average pretest score for student interest in learning using the NHT model in calculus lectures. Next is the data from the analysis of pretest and posttest scores on student satisfaction and student interest learning in calculus lectures using the NHT model using the Paired Sample T-Test showing a Sig value. (2-tailed) is .000 0.05 so H0 is rejected, which means that there is a significant difference between satisfaction using the NHT model in pretest and posttest data.